GENERASI “Z” DAN STRATEGI MELAYANINYA - Kristyowati, Yuli (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Generation Z, with its own socio-historical life in the era of the industrial revolution 4.0. Generation Z has different characteristics from the previous generation. The generation who are familiar with the internet in Indonesia has a very large number, namely 75 million people from 191.9 million productive age. Because the characteristics of this generation are very different, there is a gap with other generations. A church that does not recognize Generation Z and sticks with the old ministry style will be left behind by Generation Z. Generation Z can leave the church if it is deemed that the church does not suit the style and needs of this generation. The author conducted a non-hypothetical descriptive research with a qualitative approach method. The author uses a random sampling technique to determine the respondents, namely Generation Z, who is currently in junior high school, high school and college. The instrument for collecting data is using an open questionnaire. Advances in information technology have made no significant difference in the characteristics of Generation Z anywhere. Generation Z requires spiritual ministry with creative worship designs, teaching biblical doctrines, requires support for the formation of faith and a strong mentality, being trained to face the world by utilizing AI and building personal branding to overcome the problems and challenges of the times.